Feasibility Test on Storage Tank At PT ABC Using Asme/FFS-1 Method - Dipo Wirarchi Purboyo; Deni Ferdian; Mirza Mahendra (Publikasi Indonesia, 2023)
In the operation of oil and gas exploration and exploitation, safety is crucial as it is related to asset safety, environmental safety, and human resource safety. Storage tanks play a crucial role in the process of exploring and exploiting crude oil, serving as storage facilities for liquids in large volumes. These storage tanks are susceptible to corrosion as the materials used in their construction are typically made of steel. Uncontrolled corrosion can weaken or destroy parts of the tank system, leading to holes or structural failures that may release stored products into the environment, resulting in material losses and potential fatalities. One method for assessing the viability of pressure equipment such as pressure vessels, storage tanks, and piping systems is Fitness for Service (FFS). FFS is a quantitative engineering evaluation conducted to demonstrate the structural integrity of a component in operation, even if it has experienced damage, defects, or cracks. Guidelines in FFS procedure manuals can be used to make decisions regarding